Charles Johnson : the novelist as philosopher - Conner, Marc C., 1965-; Nash, William R., 1964- (University Press of Mississippi, 2007)
Essays by Herman Beavers, Gena Chandler, Marc C. Conner, William Gleason, William R. Nash, Linda Selzer, Gary Storhoff, and John Whalen-Bridge In Charles Johnson: The Novelist as Philosopher, leading scholars examine the African American author's literary corpus and major themes, ideas, and influences. The essays explore virtually all of Johnson's writings: each of his novels, his numerous short stories, the range of his nonfiction essays, his many book reviews, and even several unpublished works. These essays engage Johnson's work from a variety of critical perspectives, revealing the philoso.